Knowledge and awareness of MTCT and PMTCT Post-Natal follow-up services among HIV infected mothers in the Mankweng region, South Africa - Ramoshaba, Refilwe; Sithole, Sello, Levy (The open AIDS Journal, 2017)
The pandemic of Human Immunodeficiency Virus (HIV) is the most severe health challenge affecting children across the world. It is estimated that more than 90% of all HIV infections in children result from Mother-to-Child Transmission (MTCT). Poor knowledge and awareness of MTCT and Prevention of Mother-to-Child Transmission (PMTCT) among HIV positive mothers and their babies is a major setback to the success of the PMTCT programmes.
The open AIDS Journal,2017,11,36-44
Keywords: Awareness; Follow-up; Knowledge; Mother-to-Child Transmission; PMTCT; HIV (Viruses); HIV infections-Prevention.; Clinical